Characterization of Clay from Oza-Nogogo in Delta State, Nigeria for Potential Industrial Uses. - Uwadiae, S. E.; Ekeleme, V. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2018)
The aim of this study was to characterize clay from Oza-Nogogo in Delta State for its physical and chemical composition in order to assess its potential industrial applications. The clay samples were collected by means of a plastic shovel and digger, hand-picked to minimize the possibility of contamination and placed in a small polyethene bags. The samples were dried at ambient temperature for 10 days, pulverized and sieved screened to obtain fine particles before analysis. The physiochemical properties were determined using x-ray diffraction (XRD) for the mineralogical composition, X-ray florescence (XRF) for the chemical composition and Scanning Electron Microscope (SEM) for the microstructures of the clay sample. The cation exchange capacity (CEC), specific surface area and pore volume of the sample were also determined. The XRD studies showed that the clay sample is predominantly kaolinitic with some quantities of quartz, illite and feldspar. Kaolinite being the dominant clay mineral alone constitutes between 70-76% and quartz ranged from 22-28% and other minerals ranged from 1-6%. The XRF analysis showed that the sample contained high amount of silica (SiO2) by mass of 51.3% followed by Alumina (Al2O3) 40%, iron oxide (Fe2O3) 3.703%. All other minerals present were in negligible proportion. The major elemental contents of clay samples detected in the study were Si, Al, Fe, Ti and K. The SEM micrographs showed the relative sizes in the clay particles and revealed that the clay particles seem to consist of much smaller platelets which indicated that the clay sample was made up of very fine particles. The specific surface area, CEC and pore diameter were 7.846 m2/g , 6.8 meq/100 g and 28.642 nm respectively. Due to the high kaolinite content, Oza-Nogogo clay showed a potential of a basic raw material for pharmaceutical, drugs, paints, paper and ceramic industries.